Remembering Gene Wilder [videorecording (DVD)] - Wilder, Gene, 1933-2016; Alda, Alan, 1936-; Brooks, Mel, 1926- (Kino Lorber, 2024)
The loving tribute to Gene Wilder celebrates his life and legacy as the comic genius behind an extraordinary string of film roles, from his first collaboration with Mel Brooks in The Producers to the enigmatic title role in the original Willy Wonka and the Chocolate Factory to his inspired on-screen partnership with Richard Pryor in movies like Silver Streak. It is Illustrated by a bevy of touching and hilarious clips and outtakes, never-before-seen home movies, narration from Wilder's audiobook memoir, and interviews with a roster of brilliant friends and collaborators like Mel Brooks, Alan Alda, and Carol Kane. It shines a light on an essential performer, writer, director, and all-around mensch.